Influence of La substitution on local structural and photoluminescence properties of SrTiO3:Pr phosphor. (December 2018) - Deltreggia, Lucas Angelini; Bernardi, Maria Inês Basso; Mesquita, Alexandre
Abstract: Pr 3+ -doped perovskite-based SrTiO3 phosphors have been developed as a potential red phosphor. In this paper, we report the substitution of La 3+ ions for Sr 2+ ions in order to promote Sr vacancies to further enhance photoluminescence. Given that the La content increases, an enhancement in the intensity of all emissions is observed, mainly for 1 D2 – 3 H4 and 3 P0 – 3 H6 transitions. This enhancement of photoluminescence emissions is associated with disorder in the lattice caused by La incorporation. Raman measurements and X-ray absorption near edge structure (XANES) spectra at the Ti K-edge identify this disorder as a function of the La content. Graphical abstract: Unlabelled Image